Indigenist Politics in Kirchner’s Argentina - Sofía Soria (Íconos, 2019)
Navogoh and the national government that acquired particular visibility in 2010. Based on an analysis of official documents, journalistic material, speeches and interventions the actors in contention made in the public scene and the mass media, this article will explore dimensions of analysis that will make it possible to evaluate the indigenist politics from other problems: discourses that made the terms of political confrontation possible, forms of interpellation of the state, and processes of political subjectivisation. Thus, the article demonstrates how the ambiguities of a political process demand two shifts: on the one hand, to add complexity to the hypothesis of continuity; and on the other hand, to question concepts of cooptation and autonomy.